A micromechanical study of unsaturated granular material using DEM simulation and X-ray CT - Zeng, Guohan (2018)
In unsaturated soil, capillary bridges develop at the air-water interface within the pore space due to the cohesion deficiency on the side of the air phase. The interaction between capillary bridges and the soil particles make the mechanics of unsaturated soil complicated. Using the discrete element method (DEM), the behaviour of unsaturated granular materials can be predicted by including local interactions in numerical simulations. Many recent studies have been carried out to investigate the global soil properties with water-induced stresses homogeneously distributed in a granular medium. However, the quantity and spatial distribution of capillary bridges, which depends on the anisotropy and packing density of the particle arrangement, have not been well investigated. To better understand the mechanical properties of unsaturated soils, triaxial test simulations were carried out using particle assemblies with different matric suctions, varied water distribution models and various confining stresses.